Sound symbolism in Brazilian Portuguese Pokémon names: Evidence for cross-linguistic similarities and differences - André Lucas Gomes; Gakuji Kumagai; Mahayana C. Godoy; Shigeto Kawahara (Journal of Portuguese Linguistics, 2021)
Several studies in linguistics and related disciplines have been extensively exploring sound symbolism, systematic associations between sounds and meanings. Against this theoretical development, research on Pokémon names has shed new light on cross-linguistic similarities and differences in sound symbolic patterns, using similar experimental stimuli across different target languages. A recent experimental study has demonstrated that Brazilian Portuguese speakers sound-symbolically signal evolution when naming Pokémon characters: post-evolution Pokémon characters tend to receive longer names with more voiced obstruents, while pre-evolution characters tend to receive shorter names with fewer voiced obstruents. Other recent studies showed that in Japanese and English, sound symbolism can also signal differences in Pokémon type: evil-looking characters tend to be associated with voiced obstruents, while flying-type characters tend to have names with sibilants. Integrating the insights offered by these two lines of previous studies, the current paper examines whether Brazilian Portuguese speakers are sensitive to these type-related sound symbolic associations. To improve upon previous studies, we used a free-naming task in order to give participants freedom to create new names. This experiment corroborated the associations between voiced obstruents and evil-type characters, but not the association between sibilants and flying-type characters. A follow-up experiment with a forced-choice paradigm, the same method used in earlier work, also failed to reveal systematic connections between sibilants and flying-type characters. These results indicate that this association may not be universal, contrary to the claim made in previous studies.